2009
DOI: 10.1016/j.ajhg.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the SYCP3 Gene in Women with Recurrent Pregnancy Loss

Abstract: Aneuploidy, a chromosomal numerical abnormality in the conceptus or fetus, occurs in at least 5% of all pregnancies and is the leading cause of early pregnancy loss in humans. Accumulating evidence now suggests that the correct segregation of chromosomes is affected by events occurring in prophase during meiosis I. These events include homologous chromosome pairing, sister-chromatid cohesion, and meiotic recombination. In our current study, we show that mutations in SYCP3, a gene encoding an essential componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 30 publications
2
83
0
3
Order By: Relevance
“…The mutant proteins were found to interact with their wild‐type counterpart in vitro and to inhibit the normal fiber formation of the SYCP3 protein when coexpressed in a heterologous system. It is possible that the mutations generate an aberrant synaptonemal complex in a dominant‐negative manner and contribute to abnormal chromosomal behavior that might lead to recurrent miscarriage 17. These data suggest that mutations to SYCP3 induce azoospermia by meiotic arrest in men and recurrent pregnancy losses in women.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 95%
See 1 more Smart Citation
“…The mutant proteins were found to interact with their wild‐type counterpart in vitro and to inhibit the normal fiber formation of the SYCP3 protein when coexpressed in a heterologous system. It is possible that the mutations generate an aberrant synaptonemal complex in a dominant‐negative manner and contribute to abnormal chromosomal behavior that might lead to recurrent miscarriage 17. These data suggest that mutations to SYCP3 induce azoospermia by meiotic arrest in men and recurrent pregnancy losses in women.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 95%
“…In 2009, it was reported that mutations in human SYCP3 are associated with recurrent pregnancy loss 17. Two out of 26 women with recurrent pregnancy losses of unknown cause were found to carry independent heterozygous nucleotide alterations in SYCP3 , neither of which was present among a group of 150 fertile women.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 99%
“…The tissues were then cultured for 2 days as described previously 17 except that Transwell membrane inserts (polycarbonate membrane, 24-mm diameter, 3.0-mm pore size, Corning, Corning, NY, USA) and minimum essential mediumalpha medium (Invitrogen, Carlsbad, CA, USA) containing 10% fetal bovine serum, and supplemented with penicillin and streptomycin were used. For expression in mouse spermatocytes, the plasmids were introduced into the testis by in vivo electroporation as described previously, 9 and these tissues were dissected out for immunostaining 2 days later.…”
Section: Expression Of Epitope-tagged Proteinsmentioning
confidence: 99%
“…14 However, ectopically expressed SYCP3 generates a loop-like structure not only in the nucleus but also in the cytoplasm in somatic cell lines, which had not correctly reflected its intrinsic localization pattern in a previous report. 9 Therefore, in our current analyses we introduced a plasmid DNA expressing FLAG-tagged SYCP3 into adult mouse testis by in vivo electroporation. The FLAG-tagged SYCP3 protein product was detectable in the nuclei of pachytene spermatocytes by Tables 2 and 3).…”
Section: Subcellular Localization Of the Epitope-tagged Proteins Exprmentioning
confidence: 99%
See 1 more Smart Citation